FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KONSUMSI BUAH DAN SAYUR PADA PELAJAR SMPN 1 BATANG KAPAS KABUPATEN PESISIR SELATAN PADANG 2022 - Nabila Surya Madani (2022)
Lack of consumption of fruits and vegetables is one of the consumption behaviors of adolescents which is a health problem. Less consumption of fruits and vegetables can have an impact on vision health, lower immunity, anemia, constipation and other diseases. This study aims to determine the relationship between individual factors and environmental factors with fruit and vegetable consumption in students at SMPN 1 Batang Kapas in 2022. This study used a cross sectional study design conducted in March-April 2022 at SMPN 1 Batang Kapas, Pesisir Selatan, Padang. 2022 with a total sample of 106 people. The sampling technique used stratified random sampling and data analysis using univariate test and bivariate test using chi-square. Collecting data using questionnaires and SQ-Food Frequency Questionnaire. The results showed that 23.6% of students consumed the recommended amount of fruit and vegetables. From the results of the bivariate test, there was a relationship between gender (p=0.022), fruit and vegetable knowledge (p=0.012), fruit and vegetable preference (p=0.004), peer influence (p=0.032), availability of fruit and vegetables (p= 0.016), and mass media exposure (p=0.047) with fruit and vegetable consumption. This study shows that there is a relationship between gender, nutritional knowledge, fruit and vegetable preferences, peer influence, fruit and vegetable availability, and mass media exposure with fruit and vegetable consumption.